Економічні збитки від туберкульозу великої рогатої худоби в Україні - Ткаченко, Олексій Андрійович; Tkatschenko, Оleksii; Зажарський, Володимир Володимирович; Zazharskiy, Volodymyr; Алексєєва, Наталія Вікторівна; Alekseeva, Nataliya; Ковальов, Анатолій Васильович; Kovalev, A.; Зелінський, М. Д.; Zelinsky, М. (Ветінформ, 2013)
Під час багаторічних (1960-2010 рр.) ретроспективних економічних розрахунків збитків від туберкульозу великої рогатої худоби було встановлено, що частота прояву захворювання та кількість неблагополучних пунктів в Україні динамічно зменшуються, а частка основних витрат припадає на пастеризацію молока й дезінфекцію приміщень на території неблагополучних господарств. A retrospective long-term (from 1960 to 2010) economic valuation of bovine tuberculosis and found that the frequency of the symptoms of the disease and the number of troubled places in Ukraine decreased rapidly, and the share of expenditure devoted to basic pasteurization and disinfection of premises in disadvantaged households. To reduce the economic impact of tuberculosis is necessary to conduct a complete replacement of the compromised for tuberculosis population, which will increase the safety of human infection with M. tuberculosis and effectiveness of animal health, organizational and management activities in general.
Economic losses from bovine tuberculosis in Ukraine
Keywords: M. bovis; M. bovis; мікобактерії; mycobacterium; туберкульоз; tuberculosis; велика рогата худоба; cattle; економічні збитки; economic losses